Multilingualism and Change on the Kinyarwanda Sound System post-1994 - Habyarimana, Hilaire (My University, 2007)
The present study on ‘Multilingualism and change on the Kinyarwanda sound system post-1994’ focuses on sociolinguistic approaches oriented to the effects of language contact to Kinyarwanda sound change. Many studies on various multilingual societies have been conducted, and most of them have focused on multilingualism and language policy, education and social integration in different multilingual societies. In particular, most studies conducted on the new linguistic configuration of Rwanda have focused on language attitudes in a multilingual context, but none of them has tackled the issue of multilingualism and sound change as a result of language contact. The main hypothesis expounded in this research is that Kinyarwanda sound variants that can be heard from current speech arise owing to Kinyarwanda speakers’ language background. In the light of the literature review on multilingualism and sound change, an extensive analysis of the most prominent linguistic variables of sound variation in Kinyarwanda was done, and its evaluation shows that there have been shifts in the sound system of Kinyarwanda post-1994. It has been shown that some sounds were modified or shifted to other sounds which exist in neighbouring languages because of contact. In addition to that, it has been argued that this sound variation has been possible mainly because Kinyarwanda came into contact with other languages which have different sound systems. It is hoped that this research will add a new dimension to studies of multilingualism within Bantu languages and will contribute to yielding a solution to the Rwandan language problem because of suggestions related to how the Kinyarwanda sound system can be standardized.
Student Number : 0311394E - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: multilingualism; Kinyarwanda; sound system; post-1994; language policy; education; social integration; multilingual societies